2020
DOI: 10.1016/j.hrtlng.2020.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Early extubation in current valve surgery requiring long cardiopulmonary bypass: Benefits and predictive value of preoperative spirometry

Abstract: Background: Early extubation (EEx) after cardiac surgery has been essentially studied in patients with short cardiopulmonary bypass (CPB). Whether preoperative spirometry can predict EEx remains controversial. Objectives: To investigate whether EEx can be a goal and predicted by preoperative spirometry in valve surgery requiring long CPB. Methods: Nonemergent consecutive 210 patients who underwent valve surgery from January 2014 to August 2019 were investigated retrospectively. Results: EEx (<8 h) was achieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
5
1
Order By: Relevance
“…We recently demonstrated that the early extubation rate was lower after valve surgery (approximately 44%) compared with the early extubation rate after relatively simple valve surgery and CABG [ 12 ]. CPB times for our valve surgeries were longer than the CPB times in previous studies [ 13 ]; therefore, pulmonary dysfunction after CPB might contribute to prolonged DMV. In fact, CPB time was an independent predictor of prolonged DMV in several previous studies [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 85%
“…We recently demonstrated that the early extubation rate was lower after valve surgery (approximately 44%) compared with the early extubation rate after relatively simple valve surgery and CABG [ 12 ]. CPB times for our valve surgeries were longer than the CPB times in previous studies [ 13 ]; therefore, pulmonary dysfunction after CPB might contribute to prolonged DMV. In fact, CPB time was an independent predictor of prolonged DMV in several previous studies [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 85%
“…Currently, EEx is widely considered the key objective of enhanced recovery in patients who underwent heart valve surgery with CPB [ 21 ]. Hiromoto et al reported that the incidence of EEx was 44.3% for valve surgery patients receiving CPB [ 19 ]. In the aforementioned study, the percentages of patients who underwent multiple valve surgeries (3.2% vs. 8.9%), MAZE (9.7% vs. 25.0%), and tricuspid valve repair (22.6% vs. 65.2%) in the EEx (+) group were significantly lower than those in the present study; these differences could have led to the prolongation of ACC and CPB durations, thereby increasing the risk of lung damage by initiating a systemic inflammatory response, hemodilution, intrapulmonary shunt, ischemic damage, ischemia-reperfusion, and atelectasis [ 22 , 23 ], resulting in the prolongation of mechanical ventilation support.…”
Section: Discussionmentioning
confidence: 99%
“…A 44.3% incidence of EEx was assumed based on a previous study [ 19 ]. In addition, a 5% acceptable margin of error and a 95% confidence interval (CI) were used.…”
Section: Methodsmentioning
confidence: 99%
“…With relevant trial validation, Most-care has been widely used for monitoring hemodynamic variations of the CHD patients in the perioperative period. On the other hand, although the prolonged DMV is a signi cant sign of worse prognosis and successful early extubation is a goal to promote recovery after cardiac surgery with both medical and economic bene ts [13][14]23], few previous reports have a focus on the heart-lung interaction or explore the in uence of cardiac function on it. Our study initiatively found correlations between the cardiac function presented by hemodynamic parameters and mechanical ventilation status.…”
Section: Discussionmentioning
confidence: 99%